Critical analysis of hand-to-hand combat training programs for children's and youth sports schools - Radchenko , Yu. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. At the current stage of development of the sports industry, it is an indisputable fact that the longterm process of sports training from a beginner to the heights of mastery can be represented in the form of large stages that alternate in sequence, including separate stages of long-term training related to the age and qualification indicators of athletes. This whole process of long-term sports training can be conditionally divided into two stages, for each of which there are objective criteria for the effectiveness of training and organizational and methodological forms of building the training process. The first stage covers the period from the beginning of sports activities until the athlete reaches the level of higher achievements. The second stage covers the period from the athlete’s entry to the level of higher achievements to the end of his sports career. Given the realities of today, it is the first stage of the long-term training process of athletes that is reflected in the educational programs for children’s and youth sports schools. All elements and components of the process of training athletes are interconnected, mutually determined and subordinated to the task of achieving maximum sports results, and the influence of each subsequent stage is layered on the results of the previous ones, consolidating and developing them. It was assumed that solving the problem of optimizing the structure and content of the educational and training process in children’s and youth sports schools for hand-to-hand combat at the initial stage of multi-year improvement will contribute to improving the effectiveness of the process of training young athletes in various directions. The purpose of the study is to determine the peculiarities of the construction of the educational and training process in children’s and youth sports schools at the first stage of long-term training and to determine the ways of its optimisation on the basis of the analysis of the training programs of children’s and youth sports schools. Research methods: theoretical analysis and generalization of literary sources, pedagogical observation, questionnaires, methods of mathematical statistics. To achieve the goal of the work, an expert group was created, which included hand-to-hand combat trainers with the highest, first and second coaching qualifications, and four of them – Honoured Coaches of Ukraine. The results. In the course of the study, the peculiarities of construction of the educational and training process of children’s and youth sports schools in hand-to-hand combat at various stages of multi-year sports improvement were studied in detail. On the basis of the analysis, the peculiarities of the regime and the size of the groups according to the stages of training were established, the requirements for sports training according to the years of study were determined, the content and structure of competitive activities were clarified, the standards for physical and technical and tactical training were studied, and their effectiveness and informativeness at various stages of training were substantiated. Conclusions. In the process of the research, the peculiarities of the construction of the educational and training process in children’s and youth sports schools in hand-to-hand combat were determined. The theoretical and practical aspects of the scientific work presented above will be the basis for theoretical justification and further improvement of the process of training young athletes in various directions.